Multicenter prospective validation of the Baveno IV and Baveno II/III criteria in cirrhosis patients with variceal bleeding. Issue 3 (30th January 2015) - Thabut, Dominique; Rudler, Marika; Dib, Nina; Carbonell, Nicolas; Mathurin, Philippe; Saliba, Faouzi; Mallet, Alain; Massard, Julien; Bernard‐Chabert, Brigitte; Oberti, Frederic; Cales, Paul; Golmard, Jean‐Louis; et al.
Abstract : The criteria for defining failure to control bleeding in cirrhosis patients were introduced at the Baveno II/III meetings and were widely used as endpoints in clinical trials. Because they lacked specificity, the Baveno IV criteria were proposed in 2005 and slightly modified in 2010 (Baveno V). These criteria included a new index for patients undergoing transfusion, called adjusted‐blood‐requirement‐index (ABRI = number of blood units/(final‐initial hematocrit + 0.01)), with a cutoff value of 0.75. In this multicenter prospective study, we sought to 1) validate the Baveno IV/V criteria; 2) compare them to the Baveno II/III criteria; 3) assess ABRI performance using a standardized calculation. The key inclusion criteria were: 1) variceal bleeding; 2) cirrhosis; 3) no need to modify the transfusion policy. The patients were classified according to the Baveno IV, V, and II/III criteria. The gold standard for failure during a 5‐day period was the clinical judgment of three independent experts, blinded to the Baveno assessments. A total of 249 patients were included. The experts' agreement in clinical judgment of the failure was 80%. Failure occurred in 20.5% of patients; the c‐statistics were 0.72 versus 0.64 and 0.65 for Baveno IV versus Baveno II/III and Baveno V criteria ( P = 0.001 for both). ABRI did not improve the diagnostic performance of the Baveno IV criteria. The Baveno IV, but not Baveno II/III, criteria independently predicted survival. Conclusion : The Baveno IV criteria demonstrated a higher accuracy than the Baveno II/III and Baveno V criteria for assessing failure to control bleeding and predicted survival independently. Together, our results show that ABRI is not a useful metric, and the Baveno IV criteria should replace the Baveno II/III criteria. (Hepatology 2015;61:1024–1032)